Effects of young age at presentation on survival in breast cancer - Salem Ziad K (BMC Cancer, 2006)
Abstract Background Young age remains a controversial issue as a prognostic factor in breast cancer. Debate includes patients from different parts of the world. Almost 50% of patients with breast cancer seen at the American University of Beirut Medical Center (AUBMC) are below age 50. Methods We reviewed 1320 patients seen at AUBMC between 1990 and 2001. We divided them in three age groups: Below 35, 35–50, and above 50. Data and survival were analyzed using Chi-square, Cox regression analysis, and Kaplan Meier. Results Mean age at presentation was 50.8 years. 107 patients were below age 35, 526 between 35–50 and 687 patients above age 50. Disease stages were as follows: stage I: 14.4%, stage II: 59.9%, stage III: 20% and stage IV: 5.7%. Hormone receptors were positive in 71.8% of patients below 35, in 67.6% of patients 35–50 and in 78.3% of patients above 50. Grade of tumor was higher as age at presentation was lower. More young patients received anthracycline-based adjuvant chemotherapy. Of hormone receptor-positive patients, 83.8% of those below age 35 years, 87.76% of those aged 35–50 years, and 91.2% of those aged above 50 years received adjuvant tamoxifen. The mean follow up time was 3.7 +/- 2.9 years. Time to death was the only variable analyzed for survival analysis. Excluding stage IV patients, tumor size, lymph node, tumor grade and negative hormone receptors were inversely proportional to survival. Higher percentage of young patients at presentation developed metastasis (32.4% of patients below 35, as compared to 22.9% of patients 35–50 and 22.8% of patients above 50) and had a worse survival. Young age had a negative impact on survival of patients with positive axillary lymph nodes, and survival of patients with positive hormonal receptors, but not on survival of patients with negative lymph nodes, or patients with negative hormonal receptors. Conclusion Young age at presentation conferred a worse prognosis in spite of a higher than expected positive hormone receptor status, more anthracycline-based adjuvant chemotherapy and equivalent adjuvant tamoxifen hormonal therapy in younger patients. This negative impact on survival was seen in patients with positive lymph nodes and those with positive hormonal receptors.